Pendampingan Lesson Design dalam Lesson Study untuk Membangun Kolaborasi Guru SMK Muhammadiyah Pekalongan - Siti Aimah; Eny Winaryati; Muhimatul Ifadah; Riana Eka Budiastuti; Yulia Mutmainnah; Edy Sutanto; Siska Pris Setyanti; Aufa Rafika Nur (Jurnal Surya Masyarakat, 2023)
Collaboration among teachers is required to make them discuss and share their teaching experiences, including some teaching and learning problems with others. Through collaboration in lesson study, it enables them to prepare meaningful learning to students and learning of 21st century. This activity involving six English teachers of SMK Muhammadiyah Pekalongan aims to improve English teachers in designing their lesson. Through lesson study conducted in one-month, English teachers’ awareness and willingness to collaborate each other showed improvement. They became more acutely aware of the necessity to analyze students' needs when discussing issues related to teaching and learning. Additionally, they might learn something from discussing best practices in teaching through lesson study. This condition affected their ability to compose their lesson design, provide students with relevant learning experiences, and help them develop 4C (critical thinking, creative, collaboration, communication) and HOTS (high order thinking skill) skills.